Benefits of Interactive Learning for Students' Critical Thinking Skills Improvement - Tetyana Blyznyuk; Tetiana Kachak (Journal of Vasyl Stefanyk Precarpathian National University, 2024)
The article throws the light on the problem of developing students’ critical thinking skills through interactive learning. The latter offers numerous benefits for students'soft skills improvement. It requires students to actively participate in the education process, promoting engagement with the material to be gained. Interactive learning often involves problem-solving activities, which foster students to apply critical thinking skills to analyze information, evaluate results, and solve educational problems. Through hands-on experiences and real-world scenarios, students develop the ability to think critically and make informed decisions. Such active engagement encourages students to process information deeper, leading to better understanding and retention of concepts. Interaction in the learning process frequently involves collaborative activities that encourage students to work together and share ideas. Thus, collaborative learning enhances communication skills and exposes students to different perspectives, fostering critical thinking through discussions and debates. Innovative platforms aimed at interactive learning often provide immediate feedback, allowing students to assess their understanding and correct misconceptions promptly. Instant feedback facilitates a continuous learning cycle, enabling students to refine their critical thinking skills by addressing gaps in their knowledge. Interactive learning also emphasizes the application of knowledge in practical contexts. When students apply theoretical concepts to real-world situations, they simultaneously develop critical thinking skills by considering the relevance and implications of their knowledge. The authors focus on the importance on creating interactive learning environments which can be adaptable to different learning styles and paces. This adaptability encourages independent thinking and allows students to explore topics in-depth, contributing to the development of critical thinking skills. Interactive learning often incorporates multimedia resources such as videos, simulations, and interactive exercises. They provide diverse stimuli for learners, motivating critical thinking by requiring them to analyze information presented in various formats. Interactive learning can make the learning process more enjoyable and engaging for students. Considering all these aspects of arranging favorable environment for interactive learning, the authors prove the increase students’ motivation in acquiring knowledge. This leads to greater effort and persistence in students’ learning, contributing to the development and application of critical thinking skills. Thus, interactive learning activities include opportunities for reflection, where students focus on their thinking processes. Reflective practices encourage learners to evaluate their own understanding, identify areas for improvement, and refine their critical thinking strategies.